2021
DOI: 10.3390/vaccines9121448
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions towards COVID-19 Vaccines and Willingness to Vaccinate in Nepal

Abstract: Vaccination is the most effective preventive measure of COVID-19 available at present, but its success depends on the global accessibility of vaccines and the willingness of people to be vaccinated. As the vaccination rollouts are increasing worldwide, it is important to assess public perception and willingness towards vaccination, so that the aim of mass vaccination will be successful. This study aimed to understand public perception towards COVID-19 vaccines and their willingness to get vaccinated in Nepal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…It was found that 75% of the participants believed in the vaccine's efficacy. The studies conducted in Nepal (78.4%) and China (75.8%) reported similar or higher results [27,28]. Studies conducted in Pakistan and Ethiopia showed that people's perception of vaccine effectiveness was relatively low.…”
Section: Discussionmentioning
confidence: 81%
“…It was found that 75% of the participants believed in the vaccine's efficacy. The studies conducted in Nepal (78.4%) and China (75.8%) reported similar or higher results [27,28]. Studies conducted in Pakistan and Ethiopia showed that people's perception of vaccine effectiveness was relatively low.…”
Section: Discussionmentioning
confidence: 81%
“…It seemed obvious to remind each time to observe the protective measures (wearing the mask, quarantine, remote working, hygiene, vaccination, etc.). The problem is that the average population thinks that after being vaccinated it is no longer mandatory to apply preventive measures [124]. It is true that previous studies have shown that vaccination of health care workers was associated with a substantial reduction in infections [125] or that one dose of vaccine reduces the potential for transmission by 61.0% [126], but the contamination possibility still exists.…”
Section: Significance Of the Results And Health Recommendationsmentioning
confidence: 99%
“…becomes obvious. The problem is that the average population thinks that after being vaccinated, it is no longer mandatory to apply preventive measures [ 103 ]. It is true that previous studies have shown that vaccination of healthcare workers is associated with a substantial reduction in infections [ 104 ] and that one dose of vaccine reduces the potential for transmission by 61.0% [ 105 ]; however, the possibility of being infected still exists.…”
Section: Discussionmentioning
confidence: 99%